Solitary extramedullary plasmacytoma of the duodenum and pancreas – A case report and review of the literature - Ignjatović, Mile; Bezmarević, Mihailo; Cerović, Snežana (Vojnosanitetski pregled, 2017)
Introduction. The extramedullary plasmacytomas (EMPs) are rare tumors of plasma cell disorders which are rarely found in the duodenum. We presented a case of solitary EMPs involving the duodenum and pancreas successfully treated by surgical resection after failure of chemotherapy. Case report. A 55-year-old female with previously diagnosed solitary EMP of the duodenum was admitted to our institution after failure of three cycles of vincristine, adriablastine, dexamethasone (VAD) chemotherapy regimen with an upper gastrointestinal obstruction. On admission computed tomography of the abdomen showed tumor in the region of the second part of duodenum and uncinate process of the pancreas with a complete duodenal obstruction. Intraoperatively a tumor formation was in the region of the second duodenal part, originated from the wall of duodenum with the total diameter of 7 ´ 5 cm, covering the entire circumference of duodenal wall leaded to a narrowing of duodenal lumen to the thigh gap with an upper gastrointestinal obstruction. Infiltration in the head of the pancreas and uncinate process were also found. The Whipple’s procedure was performed but postoperative course was complicated by rapidly refilling chylous ascites which was resolved 4 days after the surgery. Conclusion. Each patient with gastrointestinal EMPs should be considered separately and in timely manner, thus adequate treatment could provide local disease control.
Keywords: plasmacytoma; duodenum; pancreas; intestinal obstruction; surgical procedures; operative; postoperative period; ascites; treatment outcome